2013
DOI: 10.1007/s00125-013-2982-1
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of risk factors for severe hypoglycaemia in a contemporary cohort of childhood-onset type 1 diabetes

Abstract: Aims/hypothesis Severe hypoglycaemia is a major barrier to optimising glycaemic control. Recent changes in therapy, however, may have altered the epidemiology of severe hypoglycaemia and its associated risk factors. The aim of this study was to examine the incidence rates and risk factors associated with severe hypoglycaemia in a contemporary cohort of children and adolescents with type 1 diabetes. Methods Subjects were identified from a population-based register containing data on >99% of patients (<16 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 19 publications
(38 reference statements)
10
71
5
Order By: Relevance
“…Consequently, one of the most important findings of the study was the demonstration that the lower ISPAD target of HbA 1c levels <7.5% (<58 mmol/mol) was achieved in the majority of DPV patients without increasing the risk of SH. Other current reports in children and adults support the achievement of an HbA 1c <7% (<53 mmol/mol) or <7.5% (<58 mmol/mol) without an increase in SH [11,12,20]. There is an increasing body of evidence that DKA and hyperglycaemia per se, in addition to hypoglycaemia, can have adverse effects on the developing brains of young children [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, one of the most important findings of the study was the demonstration that the lower ISPAD target of HbA 1c levels <7.5% (<58 mmol/mol) was achieved in the majority of DPV patients without increasing the risk of SH. Other current reports in children and adults support the achievement of an HbA 1c <7% (<53 mmol/mol) or <7.5% (<58 mmol/mol) without an increase in SH [11,12,20]. There is an increasing body of evidence that DKA and hyperglycaemia per se, in addition to hypoglycaemia, can have adverse effects on the developing brains of young children [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Children and Adolescents (501). In adolescents, the DCCT demonstrated that near-normalization of blood glucose levels was more difficult to achieve compared with adults.…”
Section: Diabetes Care In Specific Populationsmentioning
confidence: 99%
“…CSII may be better than MDI in selected, capable, and motivated patients with hypoglycemiaprone diabetes (70,78) largely because of the premise that CSII may reduce A1C to some extent without increasing the risk of hypoglycemia. One meta-analysis concluded that compared with MDI, CSII reduces hypoglycemia, but this conclusion was based on three randomized controlled trials using an NPH or lente insulin-based MDI regimen (79); trials using insulin analog MDI comparison groups have not reported lower rates of hypoglycemia with CSII (80)(81)(82).…”
Section: Minimizing Hypoglycemia In Diabetes General Approach To the mentioning
confidence: 99%